2013
DOI: 10.1080/15427560.2013.848867
|View full text |Cite
|
Sign up to set email alerts
|

Does Sentiment Matter for Stock Market Returns? Evidence from a Small European Market

Abstract: An important issue in finance is whether noise traders, those who act on information that has no value, influence prices. Recent research indicates that investor sentiment affects the return distribution of a few categories of assets in some stock markets. Other studies also document that US investor sentiment is contagious. This paper investigates whether Consumer Confidence (CC) and the Economic Sentiment Indicator (ESI) -as proxies for investor sentiment -affects Portuguese stock market returns, at aggregat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 40 publications
1
16
0
1
Order By: Relevance
“…Finally, Fernandes, Gonçalves, and Vieira (Fernandes et al 2013) provide an examination of the "small" Portuguese stock market. Starting from the same hypothesis of the majority of the essays cited before, they investigate whether there exists predictability not only of aggregate stock returns, but also at industrial indices levels for Portugal, over the period 1997-2009.…”
Section: Empirical Investigationmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, Fernandes, Gonçalves, and Vieira (Fernandes et al 2013) provide an examination of the "small" Portuguese stock market. Starting from the same hypothesis of the majority of the essays cited before, they investigate whether there exists predictability not only of aggregate stock returns, but also at industrial indices levels for Portugal, over the period 1997-2009.…”
Section: Empirical Investigationmentioning
confidence: 99%
“…From the economic point of view, this can be justified by the fact that Europe has not a strong financial impact comparable to the volumes of the U.S., which has been historically the leader of the worldwide markets. Fernandes, Gonçalves, and Vieira (Fernandes et al 2013) concluded that the Portuguese market has tendency to be affected by the sentiment, because of the high level of collectivism in the country. The herding is counterbalanced by the presence of institutional investors, which are considered as rational.…”
Section: The European Marketmentioning
confidence: 99%
See 1 more Smart Citation
“…It is the most widely followed measure of CC by financial analysts, the business community, policymakers and journalists (e.g. Fernandes et al 2013). Moreover, a majority of economic researchers have focused on the UMCSI because of its long history.…”
Section: Model Specification Data and Estimation Methods Model Specifmentioning
confidence: 99%
“…Regarding the Portuguese case, in a study analyzing the impact of sentiment on market returns in Portugal, using the return on the Portuguese stock market, Fernandes, Gonç alves & Vieira (2013) state that the Portuguese Economic Sentiment Indicator (ESI) and the European Union (EU) Consumer Confidence Index for Portugal are driven by rational and irrational factors. The authors only used the irrational component of sentiment, concluding that sentiment has a negative impact on future market returns and may be justified by the fact that Portugal is a market prone to the influence of sentiment as a result of its high degree of collectivism, revealing the extent to which individuals are driven to act in groups rather than individually (Hofstede, 2001).…”
Section: Literature Reviewmentioning
confidence: 99%